Unravelling the Influential Factors in the Decision-Making Process of Bank Selection Preferences among Atharvians and Their Relatives - Khadka, Puja; Bista, Sita; Panta, Sagar; Rimal, Sudhir Kumar (International Journal of Atharva, 2024)
This research investigates the complex process of bank selection among individuals and their relatives within the context of Atharva Business College. The choice of a bank is a significant decision influenced by various factors encompassing financial, social, and personal aspects. Understanding these influencing factors can enable banks to tailor their services effectively and enhance customer satisfaction. Through the use of a quantitative research approach, specifically a questionnaire survey, this study thoroughly explores the behaviours and motivations behind bank selection among those affiliated with Atharva Business College. The quantitative analysis of survey data reveals key determinants, emphasizing the relative importance of factors such as interest rates, fees, accessibility, digital banking services, and brand reputation. The findings contribute valuable insights into consumer behaviour within the banking sector, guiding banks in crafting targeted marketing strategies, improving service quality, and innovating digital solutions. Additionally, the study underscores the influence of familial connections on bank selection, highlighting the need for banks to consider the interconnected decisions of family members when developing customer engagement strategies. In conclusion, this study provides a comprehensive understanding of the bank selection process among individuals and their relatives associated with Atharva Business College.